2018
DOI: 10.1080/08952841.2018.1485387
|View full text |Cite
|
Sign up to set email alerts
|

Level of happiness and happiness-determining factors perceived by women aged over 60 years

Abstract: The aim of this article is to present the level of happiness perceived by women aged over 60 years (N = 100), to indicate the factors that determine the perception of happiness, and to determine the possibilities for strengthening the feeling of happiness. For the purposes of this article and the analysis of the obtained empirical data, the authors of this article assumed the structural theory of happiness, which allows for study participants to be viewed as biological, psychological, social, and spiritual bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
4
6
0
Order By: Relevance
“…Finding a purpose, maintaining productivity and creating goals in order to age well in the post-migration context were also important aspects for women in the study. This finding is similar to those of Janus and Smrokowska-Reichmann (2019) as well as Teater and Chonody (2020) who reported that the importance of finding a purpose and creating goals positively affected a person’s physical and mental health, thus reducing a person’s risk for loneliness and health deterioration. Janus and Smrokowska-Reichmann (2019) further explained that the key to successful aging was to create goals and work towards achieving them.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Finding a purpose, maintaining productivity and creating goals in order to age well in the post-migration context were also important aspects for women in the study. This finding is similar to those of Janus and Smrokowska-Reichmann (2019) as well as Teater and Chonody (2020) who reported that the importance of finding a purpose and creating goals positively affected a person’s physical and mental health, thus reducing a person’s risk for loneliness and health deterioration. Janus and Smrokowska-Reichmann (2019) further explained that the key to successful aging was to create goals and work towards achieving them.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is similar to those of Janus and Smrokowska-Reichmann (2019) as well as Teater and Chonody (2020) who reported that the importance of finding a purpose and creating goals positively affected a person’s physical and mental health, thus reducing a person’s risk for loneliness and health deterioration. Janus and Smrokowska-Reichmann (2019) further explained that the key to successful aging was to create goals and work towards achieving them. Creating goals was one way to maintain productivity in older adulthood which is associated with positive physical and mental health outcomes (Ruggiano et al., 2017).…”
Section: Discussionsupporting
confidence: 86%
“…This finding is reflected in the literature where older women stated that to age well, it was important to maintain good health through nutrition and physical activity (Janus & Smrokowska-Reichmann, 2018). Similarly, Gutiérrez, Tomás and Calatayud (2018) explored physical activity amongst older adults and found that older adults who maintained physical activity improved their life satisfaction, self-care, nutrition behaviours, and functional performance, thus increasing their quality of life.…”
Section: Lived Body: Aging With Gracementioning
confidence: 86%
“…This finding is similar to Janus and Smrokowska-Reichmann (2018) who conducted a qualitative study with women aged 60 and above in Poland. These older women considered themselves as being happy despite encountering barriers to achieving their goals as when they encountered as obstacle or barrier, they used this as an opportunity to restructure their goals and create new ones (Janus & Smrokowska-Reichmann, 2018).…”
Section: Lived Body: Aging With Gracementioning
confidence: 99%
See 1 more Smart Citation